PEMANFAATAN SERBUK GERGAJI PADA PERT(UMBUHAN DAN PRODUKTIFITAS JAMUR TIRAM PUTIH (Pleurotus ostreatus) DI DESA TU’INDRAO KECAMATAN AMANDRAYA KABUPATEN NIAS SELATAN - Giawa, Hendrikus (Universitas Nias Raya, 2024)
The research objectives are know how to make white oyster mushroom white by using powder wood saw utilizing powder chainsaw at seedlings plants oyster mushrooms, to determine growth and productivity oyster mushroom white Research method this is by method descriptive with a qualitative approach, describe, analyze phenomena on the object of research. This type of research is powder utilization chainswa wood to growth and productivity mushroom oysters white in Tu'indrao village, Amandraya findings research i.e, making media mushroom by preparing 100 kg powder and mixed with other ingredients, utilitazion powder chainsaw with the inoculation stage f2 mushroom spawn number ±1-2 spatula, growth and productivity mushroom oysters 1-2 days after inoculation to grow fruit, 3-5 days harvest mushroom, yield 5 kg per 1 harvest and ready to be utilized by the community as a vegetable. Research from conclusion this is utilizing media powder chainsaw wood for mold growth oysters is, before the media is mixed it should be powder chainsaw composted and sterilized especially first to makes the texture softer my suggestions in research this is, this research is expected to be an alternative to develop other research that related with cultivation mushroom oysters white (Pleurotus ostreatus) by using powder chainsaw wood. For students, as source knowledge in carrying out learning activities at eyes taxonomy lecture plants level low in program study education biology.